2009
DOI: 10.1159/000238401
|View full text |Cite
|
Sign up to set email alerts
|

Expressive and Receptive Language Characteristics in Three-Year-Old Preterm Children with Extremely Low Birth Weight

Abstract: Objective: The purpose of this study was to analyze the language characteristics of a group of extremely low birth weight (ELBW) children at 3 years of age and to compare these language results with a sample of full-term children with normal birth weight (FBW). Methods: All children were judged to be free of any major physical, sensorial and neurological impairments and had a mental developmental index of >55 on the Bayley Scales of Infant Development. The Language was tested using the Reynell Developmental La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 11 publications
0
21
0
1
Order By: Relevance
“…Studies on communicative -linguistic development found that preterm children have problems in auditory discrimination in the first days of life, and at 4 and 5 years old (53,55,62), problems in grammar skills at 2, 3, 5 and 6 years old (47,50,55,57,59,61,64), problems in naming objects and words at 4 and 5 years old (55,62,63,64) and pre-reading skills at 6 years (64). Other studies found that these children have no problems in lexical production at 4 years old (62).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on communicative -linguistic development found that preterm children have problems in auditory discrimination in the first days of life, and at 4 and 5 years old (53,55,62), problems in grammar skills at 2, 3, 5 and 6 years old (47,50,55,57,59,61,64), problems in naming objects and words at 4 and 5 years old (55,62,63,64) and pre-reading skills at 6 years (64). Other studies found that these children have no problems in lexical production at 4 years old (62).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no conclusive data about problems in expressive and receptive language develop-ment in general, vocabulary size and communication skills. Some studies found that preterm children have problems in expressive and receptive language development in general in the first two years of life, and from 2 to 6 years of age (40,48,52,54,61,62,65). One study found that preterm children have no problems in expressive and receptive language development in general at 5 years (63) and other study found that these children have problems in some specific components of expressive language (sentences), but they do not have problems in other components (information) at 3 years old (60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have used the corrected age for prematurity to verify the performance for functional abilities in varied developmental areas 22,28 ; however, it is worthy pointing that there is no consensus regarding the use of the corrected age for the assessment of the prematurity effects in different development dimensions 18,23 . This is justified, since the use of the corrected age could put premature children in normative baselines, in a first analysis and, then, postpone preventive measures for a full development 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported that premature children may show delay in receptive language and in expressive language 2,19 . Regarding the communicative abilities, literature also shows the affected areas in premature refer to linguistic abilities, to vocabulary, to grammar and phonological awareness, which are usually less developed when compared to the development of children who were born at term 3,[14][15][16][19][20][21][22][23][24][25][26][27][28][29][30][31] . Given the above, this study purpose was to compare the development of communicative abilities in children who were born premature, extreme premature and typical children with chronological age between two and three.…”
Section: Casuistic Characterizationmentioning
confidence: 99%